2019
DOI: 10.1038/s41598-019-43139-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity profiling of protein antigens from capsular group B Neisseria meningitidis

Abstract: Outer membrane vesicle (OMV)- based vaccines have been used to provide strain-specific protection against capsular group B Neisseria meningitidis infections, but the full breadth of the immune response against the components of the OMV has not been established. Sera from adults vaccinated with an OMV vaccine were used to screen 91 outer membrane proteins (OMPs) incorporated in an antigen microarray panel. Antigen-specific IgG levels were quantified pre-vaccination, and after 12 and 18 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
(106 reference statements)
1
18
0
Order By: Relevance
“…Among them, OMV minor antigens are known to play a synergistic role in the cross-bactericidal activity. In a recent study, sera from adults vaccinated with an OMV vaccine were used to screen an antigen microarray containing 91 outer membrane proteins 27 . The authors identified six very high responding antigens corresponding to OMVs components that could play a role in the protective immune response induced by OMV based vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, OMV minor antigens are known to play a synergistic role in the cross-bactericidal activity. In a recent study, sera from adults vaccinated with an OMV vaccine were used to screen an antigen microarray containing 91 outer membrane proteins 27 . The authors identified six very high responding antigens corresponding to OMVs components that could play a role in the protective immune response induced by OMV based vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, a faster and more powerful technology to perform epitope mapping is represented by protein microarrays, which allow analysing simultaneously short and long peptides that are representative of all immunogenic regions of an antigen, including both linear and conformational epitopes, with the further advantage of using only minimal volumes of biological samples. Proteomic microarrays generated by spotting full-length antigens are largely used to profile responses to bacterial infections 25 , 26 or following vaccination 27 29 or as diagnostic tool 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Even among immunised children with culture-confirmed IMD, we have a poor understanding of which vaccine antigens are important for protection, whether some of the vaccine antigens offer more protection than others or whether some combinations of vaccine antigens might be more protective than others through synergy, for example. At the same time, in addition to harbouring the immunodominant PorA 1.4 antigen, the OMV component of 4CMenB has multiple minor antigens which also help protect against IMD, but their contribution is difficult to measure 51. There are currently no data to suggest that breakthrough MenB cases in immunised children are associated with an underlying immune deficiency or an increased risk of recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins play a role in bacterial membrane metabolism and functions, in pathogenesis by mediating host cell adhesion and inflammatory responses and are considered good vaccine candidates [95]. Examples in Neisseriae include established vaccine targets (factor H binding protein (fHbp) part of both Bexsero and Trumenba [92,96]) and preclinical targets (reviewed in Reference [97]), for example TbpB [25], NMB0928 [70,73] (homolog of NGO0948), MetQ [30,34]. Two candidates were potentially involved in metal binding, NGO1215 (AccA [86]), and NGO1701 (hypothetical).…”
Section: Discussionmentioning
confidence: 99%
“…(2) NGO0690, a putative P/OM lipoprotein, possibly involved in threonine biosynthesis and pilin antigenicity [67]; (3) NGO0948, a P/OM lipoprotein member of the NlpB/DapX family (COG3317), homolog to BamC (a member of the BAM complex [68], surface-exposed in E. coli [69]) and a potential meningococcal vaccine antigen (NMB0928 [70][71][72][73]); (4) NGO1043, a hypothetical P/OM putative lipoprotein, possibly glycosylated and a substrate for phosphoethanolamine (PE) addition [74,75], with homology to the meningococcal antigen Ag473 [76]; (5) NGO1215, a hypothetical P protein with homology to a copper chaperone PCu(A)C superfamily (COG2847) (potential virulence factors) [77] and reported as AccA [78], and (6) NGO1701, a P membrane protein with homology to a TAT_Cys_rich four helix bundle copper-binding protein of the DUF326 superfamily. Table 1 summarizes the major CASS features for these candidates.…”
Section: Discovery and Analysis Phase (Dap)mentioning
confidence: 99%